2019
DOI: 10.1016/j.jpainsymman.2018.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Simulation-Based Mastery Learning Curriculum for Breaking Bad News

Abstract: Introduction. Physician communication impacts patient outcomes. However, communication skills, especially around difficult conversations, remain suboptimal, and there is no clear way to determine the validity of entrustment decisions. The aims of this study were to 1) describe the development of a simulation-based mastery learning (SBML) curriculum for breaking bad news (BBN) conversation skills and 2) set a defensible minimum passing standard (MPS) to ensure uniform skill acquisition among learners. Innovatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 13 publications
(15 reference statements)
0
35
0
Order By: Relevance
“…Additionally, there are few studies in the simulation-based mastery learning literature that evaluate practicing attending physicians' performance and require them to meet or exceed an minimum passing standard. 18,19 Our study adds to the growing body of literature that already demonstrates simulation-based mastery learning has the potential to improve clinical skills [7][8][9][10][11][12] and patient outcomes, 9,20 as well as providing a positive return on investment. 21,21,22,22,23 In contrast with previous studies, 7,10,24 we showed modest correlations between simulated test performance and the number of procedures performed in practice and self-confidence.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Additionally, there are few studies in the simulation-based mastery learning literature that evaluate practicing attending physicians' performance and require them to meet or exceed an minimum passing standard. 18,19 Our study adds to the growing body of literature that already demonstrates simulation-based mastery learning has the potential to improve clinical skills [7][8][9][10][11][12] and patient outcomes, 9,20 as well as providing a positive return on investment. 21,21,22,22,23 In contrast with previous studies, 7,10,24 we showed modest correlations between simulated test performance and the number of procedures performed in practice and self-confidence.…”
Section: Discussionmentioning
confidence: 78%
“…Despite this, a significant amount of research has already shown that simulation-based mastery learning improves physicians' skills and patient care outcomes. [7][8][9][10][11][12] The control for the study was each participants' pretest score and therefore, each individual served as their own control (quasi experimental design). A formal controlled trial was not performed because every anesthesiologist needed to be trained quickly to evaluate the clinical effects of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the residency progresses, students understand that asking for help is a basic component of the general clinical practice and specifically of anesthesiology. Communication skills are fundamental and impact numerous health outcomes, including trust in clinicians, satisfaction, and even patient and family quality of life [ 18 20 ]. Therefore, training in communication skills is crucial to improve them [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a large and growing body of evidence supporting the use of SBML as an educational modality for acquiring technical and procedural skills [27][28][29][30][31][32]. However, SBML has less frequently been used for acquisition of communication and interpersonal skills [33,34]. SBML is time and resource intensive, as one of the main means by which trainees acquire mastery is through repeated deliberate practice.…”
Section: Introductionmentioning
confidence: 99%